2020
DOI: 10.3390/nu12020564
|View full text |Cite
|
Sign up to set email alerts
|

Increased Colonic Permeability and Lifestyles as Contributing Factors to Obesity and Liver Steatosis

Abstract: Intestinal permeability (IP) is essential in maintaining gut-metabolic functions in health. An unequivocal evaluation of IP, as marker of intestinal barrier integrity, however, is missing in health and in several diseases. We aimed to assess IP in the whole gastrointestinal tract according to body mass index (BMI) and liver steatosis. In 120 patients (61F:59M; mean age 45 ± SEM 1.2 years, range: 18–75), IP was distinctively studied by urine recovery of orally administered sucrose (SO, stomach), lactulose/manni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 86 publications
3
44
1
1
Order By: Relevance
“…We assessed urine recovery of orally administered sucrose, lactulose/mannitol, and sucralose by using triple quadrupole mass-spectrometry and high-performance liquid chromatography. We found that increased colonic (but not stomach and small intestinal) permeability was linked to obesity and liver steatosis, regardless dietary habits, age, and physical activity [ 167 ] ( Figure 6 ).…”
Section: Beyond Nafld: the Gut Liver-axis The Gut Barrier And Thmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed urine recovery of orally administered sucrose, lactulose/mannitol, and sucralose by using triple quadrupole mass-spectrometry and high-performance liquid chromatography. We found that increased colonic (but not stomach and small intestinal) permeability was linked to obesity and liver steatosis, regardless dietary habits, age, and physical activity [ 167 ] ( Figure 6 ).…”
Section: Beyond Nafld: the Gut Liver-axis The Gut Barrier And Thmentioning
confidence: 99%
“…Their presence in urine, in different amounts compared to the expected, indicated impaired permeability of the stomach, small intestine, or colon. Normal values for permeability test are expressed as a percentage) adapted from Di Palo et al [ 167 ]).…”
Section: Figurementioning
confidence: 99%
“…(A) Initial role of wrong lifestyles (hypercaloric, unbalanced, fructose‐ and refined carbohydrate‐enriched diet, sedentary behaviour), on a genetic/racial, ethnical and environmental background. Changes in intestinal microbiota can also govern additional metabolic changes due to biotransformation of foods, local inflammatory changes, increased intestinal permeability 112 to bacterial products (ie lypopolisaccharides). (B) Expansion of visceral fat may occur in different phenotypes, independently of simple body weight (encompassing the term 'adiposity' or 'overfat').…”
Section: Introductionmentioning
confidence: 99%
“…The malabsorption and the altered intestinal microbiota might facilitate, in patients with SIBO, the diffusion of products deriving from bacterial metabolism through the blood stream, thus contributing to the dissemination of pathogen associated molecular patterns (PAMPs) [ 162 , 163 ]. This condition might also interfere with a physiological intestinal permeability [ 164 ] as well as with the bioavailability of drugs [ 165 ]. SIBO could be responsible of unresponsiveness to colchicine, while SIBO decontamination therapy with rifaximin, a non-absorbable antibiotic, contributed to a decrease in FMF attacks [ 166 ].…”
Section: Gene-bacteria Interplay and Composition Of Gut Microbiotamentioning
confidence: 99%